PENGARUH IKLIM ORGANISASI, KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT.ADIKA JAYA DEWATA DENPASAR - I Putu Andika Adi Guna; I Ketut Setia Sapta; I Gede Rihayana (VALUES, 2022)
Human resources are one of the important elements in driving the progress of an organization. Employees who have the ability to carry out their duties and responsibilities well can help the organization to continue to grow and develop. Employee performance plays an important role in an organization. This also happened to PT. Adika Jaya Dewata Denpasar, therefore this study aims to determine the effect of organizational climate, work ability and work motivation on employee performance at PT. Adika Jaya Dewata Denpasar. The population of this study were all employees of PT. Adika Jaya Dewata Denpasar which reached 110 people, so the number of sample members was 40 people as respondents. The analytical tool used to test the hypothesis is multiple linear regression analysis. Based on the results of the analysis shows that the organizational climate has a positive and significant effect on employee performance. That is, the better the organizational climate, the better the performance of employees, and vice versa if the organizational climate is not good, it will have an impact on decreasing employee performance. It is the same with work ability which has a positive and significant effect on employee performance, meaning that if work ability then employee performance will increase, on the contrary if work ability is poor then employee performance will decrease and the same is the case with work motivation which has a positive and significant effect on employee performance, meaning if employees have good work motivation then employee performance will increase, and vice versa if there is a decrease in work motivation by employees it will have an impact on decreasing employee performance.